2007
DOI: 10.1080/13607860601086561
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and physical health of family caregivers for persons with dementia: A comparison of African American and white caregivers

Abstract: This investigation analyzed the differences between African American and white caregivers in the effects of family caregiving for a person with dementia on mental health and physical health variables (including subjective health, reported diseases and cardiovascular measures). A population-based sample of 102 caregivers is compared with 102 non-caregivers matched on ethnicity, gender and age. There were no significant group differences for mental health effects. Most significant physical health effects were at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Although high rates of depression among caregivers have been reported, estimates vary widely and elevated rates are largely based on helpseeking samples. A recent population-based study found no differences in depression between caregivers and non-caregivers matched for ethnicity, gender and age (Knight, Flynn Longmire, Dave, Kim, & David, 2007). Aspects of the care recipient's illness are related to depression in the caregiver.…”
Section: Etiology and Risk And Protective Factorsmentioning
confidence: 99%
“…Although high rates of depression among caregivers have been reported, estimates vary widely and elevated rates are largely based on helpseeking samples. A recent population-based study found no differences in depression between caregivers and non-caregivers matched for ethnicity, gender and age (Knight, Flynn Longmire, Dave, Kim, & David, 2007). Aspects of the care recipient's illness are related to depression in the caregiver.…”
Section: Etiology and Risk And Protective Factorsmentioning
confidence: 99%
“…Much research has been devoted to describing changes in the mental health of family members who provide care to older parents in a variety of populations around the world (Butler, Turner, Kaye, Ruffin, & Downey, 2005;Knight, Longmire, Dave, Kim, & David, 2007;Morano, 2003;Raveis, Karus, & Siegel, 1998;Schulz & Sherwood, 2008). Less attention has been paid to the impact that cultural values may have on the mental health of family caregivers.…”
Section: Introductionmentioning
confidence: 98%
“…In particular, some researchers have found Black caregivers report lower mean levels of depression (Clay, Roth, Wadley, & Haley, 2008; Sleath, Thorpe, Landerman, Doyle, & Clipp, 2005; Sorensen & Pinquart, 2005), while other researchers have found that Black and White caregivers have similar mean levels of depressive symptoms (Hinrichsen & Ramirez, 1992; Knight, Flynn Longmire, Dave’, Kim, & David, 2007; Knight & McCallum, 1998). Overall, Black caregivers appear to have lower or equal, but not higher, levels of depression than White caregivers.…”
Section: Introductionmentioning
confidence: 99%